The armed conflict component of war crimes - Redouane, Mohamed Belkacem (Journal of Human Sciences, 2023)
War crimes have a special regime compared to other international crimes in the sense that they must be linked to the element of armed conflict and this in accordance with the principles of the law of armed conflict and international criminal law, for the possibility to exercise international criminal jurisdiction or the reunification of its constituent elements as proof of the commission of these crimes in the context of any armed conflict.       The main objective of this article is to give an in-depth analysis of this element of "Armed Conflict" either as a prerequisite for the exercise of jurisdiction over these crimes, or as a major component of the elements of the crime itself, and this can only be achieved by analyzing the viewpoints of international criminal justice, whether through what has been adopted in the status and its annexes of international criminal jurisdictions or what has been adopted through the decisions and jurisprudences of those instances.